Bach and Busoni Essentials in A Chaotic World - Lee, Seow Phing; Ooi, C. H. Raymond; Cheong, Ku Wing (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2021)
The study analyses the manifestation of structural change from the Bach Violin Chaconne (BWV1004, c.1720) to the Bach-Busoni piano transcription (c.1897). This article explores the use of two-dimensional music abstraction for vertical (pitch height) and horizontal (time) and its signal insignificant identified bariolage sections in music. Bariolage excerpts are chosen for they are implied sounds captured in repeatability and recontextuality. The first part of the article offers an excerpt of the Bariolage from violin at bars (113-120) and its parallel piano transcription at bars (118-125). Significant expressions of registral change utilizing different voice parts (Soprano, Alto, Tenor) offer a wider expansion with piano. These excerpts were chosen after reviewing the original Bach Chaconne and its essentials in analytical aesthetics for the projection of beauty in symmetry-asymmetry-chaos in composition. This study captures the aesthetics of the beautiful from the original score of the violin Chaconne at (bars 89-96) and (bars 113-120) for Bach-Busoni piano transcription. Further, there are recommendations for future studies to explore vertical spaces and mathematical sequences embedded in the music in other sections. The findings of this study were implied through new music analytical formats to be applied in composition, pedagogy, and performance practice.Ã‚Â